2003
DOI: 10.1074/jbc.m303000200
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Yeast Prion Ure2p into Protein Fibrils

Abstract: The [URE3] phenotype in Saccharomyces cerevisiaepropagates by a prion mechanism, involving the aggregation of the normally soluble and highly helical protein Ure2. Previous data have shown that the protein spontaneously forms in vitro long, straight, insoluble fibrils at neutral pH that are similar to amyloids in that they bind Congo red and show green-yellow birefringence and have an increased resistance to proteolysis. These fibrils are not amyloids as they are devoid of a cross-␤ core. Here we further docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…This indicates that five Ure2p molecules are sequestered in an assembly-incompetent state by each molecule of Ssa1p. We previously showed that hexameric Ure2p is the precursor of the fibrillar form of the protein (27,33). Thus, our results strongly suggest that Ssa1p binds to the hexameric form of Ure2p.…”
Section: Nature Of the High Molecular Weight Ure2p Species That Form supporting
confidence: 69%
See 2 more Smart Citations
“…This indicates that five Ure2p molecules are sequestered in an assembly-incompetent state by each molecule of Ssa1p. We previously showed that hexameric Ure2p is the precursor of the fibrillar form of the protein (27,33). Thus, our results strongly suggest that Ssa1p binds to the hexameric form of Ure2p.…”
Section: Nature Of the High Molecular Weight Ure2p Species That Form supporting
confidence: 69%
“…Because Ure2p assembly into protein fibrils is irreversible (27) if Ure2p fibrils were indeed severed by Hsp104p, one would expect to generate shorter fibrils, but the overall amount of fibrils should not change. Fibrillar material should be, therefore, detected trapped to the cellulose acetate filters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another commonly described feature is that the length of the lag time decreases with increasing protein concentration in an approximately exponential relationship. In fact, for Ure2 [36,102] and also for Sup35 [103], the relationship between increasing protein concentration and decreasing lag time is linear. This may reflect a variation in mechanism, the oligomeric nature of the native state, or simply the choice of reaction conditions [36,101,103].…”
Section: Relationship Between Folding and Amyloid Formationmentioning
confidence: 93%
“…На основании этого можно предположить, что размер критического ядра для образования наноамилоидной формы Аb будет больше четырёх или семи. Для белка Ure2p было найдено, что размер критического ядра состоит из шести цепей, варьируя лаг-период за счет изменения концентрации белка [69]. Из-за сложности задачи эти данные не были подтверждены теоретическими расчётами.…”
Section: идентификация сайтов в белковой цепи ответственныхunclassified